2009
DOI: 10.1021/mp900215p
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hydrogel Nanoparticle Size and Functionalization on In Vivo Behavior for Lung Imaging and Therapeutics

Abstract: Polymer chemistry offers the possibility of synthesizing multifunctional nanoparticles which incorporate moieties that enhance diagnostic and therapeutic targeting of cargo delivery to the lung. However, since rules for predicting particle behavior following modification are not well defined, it is essential that probes for tracking fate in vivo are also included. Accordingly, we designed polyacrylamide-based hydrogel particles of differing sizes, functionalized with a nona-arginine cell-penetrating peptide (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 51 publications
3
77
0
2
Order By: Relevance
“…As expected, for non-specific uptake of the nanocomplexes of antisense and mismatched PNAs and non-specific clearance from uninduced cells, the biodistribution in the non-targeted organs showed similar profiles at both 4 and 24 h. Accumulation of radioactivity in the thyroid, liver and kidney is likely due to transit from the air space through the alveolar epithelium-capillary endothelial barrier [54], which was also confirmed by measurable activity in the blood at 4 and 24 h p.i. Similar to the reported extra pulmonary fate of nanoparticles, following intratracheal instillation [51,55], significant amounts of gastrointestinal tract clearance were observed for both nanocomplexes, likely due to mucociliary clearance. Recently, a report showed that the translocation of nanoparticles from the lung airspace to the body was sizedependent, irrespective of chemical composition, shape and conformational flexibility.…”
Section: Rsfsroyalsocietypublishingorg Interface Focus 3: 20120059supporting
confidence: 77%
“…As expected, for non-specific uptake of the nanocomplexes of antisense and mismatched PNAs and non-specific clearance from uninduced cells, the biodistribution in the non-targeted organs showed similar profiles at both 4 and 24 h. Accumulation of radioactivity in the thyroid, liver and kidney is likely due to transit from the air space through the alveolar epithelium-capillary endothelial barrier [54], which was also confirmed by measurable activity in the blood at 4 and 24 h p.i. Similar to the reported extra pulmonary fate of nanoparticles, following intratracheal instillation [51,55], significant amounts of gastrointestinal tract clearance were observed for both nanocomplexes, likely due to mucociliary clearance. Recently, a report showed that the translocation of nanoparticles from the lung airspace to the body was sizedependent, irrespective of chemical composition, shape and conformational flexibility.…”
Section: Rsfsroyalsocietypublishingorg Interface Focus 3: 20120059supporting
confidence: 77%
“…Most of the studies of low-toxicity nanomaterials have been conducted using rigid, crystalline, insoluble materials, whereas there has been less research on the response of the respiratory system to the administration of organic nanomaterials (Beyerle et al, 2011;Dailey et al, 2006;Harush-Frenkel et al, 2010;Liu et al, 2009;Nassimi et al, 2009), sometimes referred to as soft nanomaterials (Nalwa, 2009). Organic nanomaterials are increasingly being developed as inhaled nanomedicines or components of aerosol-based consumer products, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…7.3). These studies indicate the potential of microparticles for short-term applications as well as the benefits of nanoparticles for serial imaging or therapy of a persistent lung injury [131]. In contrast, a study of acute lung injury used latex nanoparticles coated with antiintercellular adhesion molecule-1(ICAm-1) antibody and labeled with 64 Cu for targeting the pulmonary endothelium.…”
Section: Radiolabeled Polymeric Nanoparticles For Pet Imagingmentioning
confidence: 99%